2022
DOI: 10.30684/etj.2022.135475.1274
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of a Counter-Flow Double-Pass Solar Air Heater With The Steady and Pulsating Flow

Abstract:  The tubular solar absorber is placed perpendicularly to the direction of airflow.  Pulsating flow increases the thermal performance by up to 15.2%  Thermal performance is directly proportional to the pulsating frequency.The present work studied the influence of pulsating flow as an active method on the thermal performance of a double-pass solar air heater with a tubular solar absorber. A ball valve has been used as a pulse generator mounted at the downstream flow of the solar air heater. The experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In both instances, black paint with 2% nanomaterial incorporated in it is employed as a coating agent. Hussein et al 19) investigated the effect of pulsing flow as an active technique on the thermal efficiency of a double-pass SAH using a tubular solar absorber. Based on the results of the experiment, it was concluded that applying pulsing flow increases the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In both instances, black paint with 2% nanomaterial incorporated in it is employed as a coating agent. Hussein et al 19) investigated the effect of pulsing flow as an active technique on the thermal efficiency of a double-pass SAH using a tubular solar absorber. Based on the results of the experiment, it was concluded that applying pulsing flow increases the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%